Cuteness or Coolness—How Does Different Anthropomorphic Brand Image Accelerate Consumers’ Willingness to Buy Green Products? - Lu, Yue; Liu, Yunxiao; Tao, Le; Ye, Shenghong (Frontiers in Psychology, 2021)
Green consumption is an important component of environmental protection behavior. The behaviors of individual consumers are having unprecedented impacts on the sustainable development of green society. Previous researches have discussed how anthropomorphic beneficiaries of environmental behavior (e.g., nature/earth) impact green consumption behavior and compared the influence of anthropomorphic presence and absence on consumers. However, few have examined the impact of different types of anthropomorphic carrier with environmental benefits (e.g., green product/brand) on consumers. This research explores the matching effects on consumers' willingness to buy green products between anthropomorphic image of the brand (cute vs. cool) and advertising appeals (self-interest vs. altruism); in addition, the underlying mechanisms of matching effects are revealed. The results show that under the self-interested advertising appeal, the cool anthropomorphic image can lead to higher purchase intention of green products due to the mediating role played by brand capacity trust. However, when exposed to altruistic advertising appeal, the cute anthropomorphic image can enhance consumers' brand goodwill trust and make consumers more willing to buy green products. Finally, this paper discusses the contributions and limitations.